Partisipasi Masyarakat dalam Pembangunan Desa di Desa Merbaun, Kecamatan Amarasi Barat, Kabupaten Kupang Berdasarkan Undang-Undang Nomor 6 Tahun 2014 - Robertho Puay; Yohanes G.T Helan; Cyrilius W. T. Lamataro (Lembaga Pengembangan Kinerja Dosen, 2025)
Development through community participation in villages is one of the efforts to empower the potential of village communities in planning development related to local resource potentials. The research questions in this study are: (1) How is the community participation in the development of Merbaun Village, West Amarasi Subdistrict, Kupang Regency? (2) What factors may hinder the success of community participation in village development in Merbaun Village, West Amarasi Subdistrict, Kupang Regency? This research is a juridical-empirical study with a qualitative approach, using primary data collection techniques through interviews. Secondary data was obtained through literature studies. The results of the study show that community participation in Merbaun Village development can be analyzed through three stages: planning, implementation, and supervision. Each stage shows different dynamics and levels of participation. (1) Planning Stage: At this stage, community participation is considered high. The village government conducts a development planning deliberation (Musdus) to absorb the aspirations of the community. Interview results show that the community is actively providing input and suggestions, reflecting a strong motivation and concern for the proposed development programs. (2) Implementation Stage: In contrast to the planning stage, the level of community participation in the implementation of development drops significantly. Although the village government opens opportunities for mutual cooperation (gotong-royong), community attendance is inadequate, with many absent. This indicates a lack of understanding and awareness among the community regarding the importance of their participation in the physical activities that have been agreed upon. (3) Supervision Stage: The supervision of the development also shows a lack of participation. The community should be involved in monitoring and evaluating development programs. However, most of the community members do not understand their role in the supervision process, as revealed in the interviews.The study suggests that community participation in the development of Merbaun Village should be increased to make development outcomes more effective and sustainable, in accordance with the principles outlined in Law Number 6 of 2014 concerning Villages.